2021
DOI: 10.4103/ua.ua_117_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the urology residency training program in Saudi Arabia

Abstract: Purpose: This study evaluates the satisfaction of urology residents with the Saudi Board of Urology (SBU) Training Program and identifies areas of weakness and strength to improve the educational environment, surgical competency, and overall satisfaction of urology residents with the program. Methods: We administered an electronic self-made questionnaire that included two sections. One comprised demographic data (age, gender, weight, height, marital status, level of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Around one third of participants were unsatisfied with the residency curriculum. It is hypothesized that ineffective curriculum development in terms of irrelevant content to the practice, not engaging residents, and unsuccessful curriculum execution could contribute to their dissatisfaction (AlShareef, 2014;Alkhamees et al, 2021). Moreover, a higher number of teaching activities per week seems to be associated with a notable level of satisfaction Recommendations to improve the residency program.…”
Section: Discussionmentioning
confidence: 99%
“…Around one third of participants were unsatisfied with the residency curriculum. It is hypothesized that ineffective curriculum development in terms of irrelevant content to the practice, not engaging residents, and unsuccessful curriculum execution could contribute to their dissatisfaction (AlShareef, 2014;Alkhamees et al, 2021). Moreover, a higher number of teaching activities per week seems to be associated with a notable level of satisfaction Recommendations to improve the residency program.…”
Section: Discussionmentioning
confidence: 99%
“…Residents specializing in Saudi Specialty Certificate programs requiring five years or longer, such as general surgery, neurosurgery, plastic surgery, orthopedic surgery, ear, nose, and throat (ENT), cardiac surgery, urology, obstetrics and gynecology (OBGYN), and anesthesia, were more likely to express a preference for their specialty based on genuine passion for the practice. These specialties, historically associated with reduced work-life balance [24][25][26][27], tend to attract residents who prioritize the inherent rewards of the field.…”
Section: Discussionmentioning
confidence: 99%
“…A study of pediatric surgery residents also found a high satisfaction rate [ 17 ]. On the other hand, satisfaction scores with regards to the training among urology residents are divergent across the literature, ranging from less than 30% to more than 80% [ 18 , 19 ]. Similarly, publications show a varying level of satisfaction for plastic and reconstructive surgery residents across institutions of study [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%